Spetsificheskie izmeneniya v metabolizme sportsmenov, treniruyushchikhsya v raznykh bioenergeticheskikh rezhimakh, v otbet standartnuyu fizicheskuyu nagruzku - Suzdalnitskij, R. S.; Menshikov, I. V.; Modera, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this study was to discover some specific alterations in metabolism of athletes who are training in various bioenergetical regimes. Authors' special attention was paid to the research of peculiarities of substrative suppliement and its regulation mechanisms. The marks were chosen accordingly - glucose, fat acids, hormones, cortifan, insulin, ionized calcium and others. At the end of the research it was shown at the first time that in conditions of originality of adoptive systems formation and in dependence on bioenergetical regimes of training, even a single standard physical load (PWC 170) intails specific alterations in athletes' metabolism. The alterations in correlation of cortifan, insulin, ionized calcium could be recognized as the mark of energy supplying system efficiency, as the mark of good-training and as the mark of reaction's adequacy to the load.